Petrogenesa Batuan Beku Daerah Garapia Kecamatan Monano Kabupaten Gorontalo Utara Provinsi Gorontalo - Karim, Susilawati; Permana, Aang Panji; Ninasafitri, Ninasafitri (-, 2025)
This study aims to examine the petrogenesis of igneous rocks exposed in the Garapia area, Anggrek District, North Gorontalo Regency, in order to identify their distribution, geochemical characteristics, and tectonic setting. The research methods included field survey, sample collection,petrographic analysis, and laboratory analysis using X-Ray Fluorescence (XRF), followed by CIPW normative calculation and construction of discrimination diagrams (QAPF, AFM, Harker). Petrographic analysis shows that the rocks are dominated by plagioclase (60–65%), quartz (10–15%), and pyroxene (20–25%), with minor accessory minerals. Mineral normalization places sample RK-01 in the basaltic andesite group, while sample RK-12 is classified as andesite. Normative CIPW analysis indicates the presence of normative quartz and labradorite as the dominant plagioclase, reflecting silica-oversaturated characteristics. Plotting on the AFM diagram (Irvine Baragar, 1971) places the samples within the tholeiitic to calc-alkaline series. Overall, the results confirm that the igneous rocks in the Garapia area were formed in a volcanic arc magmatic environment, with magma evolution controlled by fractional crystallization of plagioclase and pyroxene, as well as magma differentiation processes that produced compositional variations from basalt to andesite.